Reaksi Pasar terhadap Peristiwa Politik 2019 di Indonesia - Kemuning, Ni Luh Dea; Prianthara, Ida Bagus Teddy; Wistawan, I Made Andika Pradnyana (E-Jurnal Akuntansi; Vol 31 No 7 (2021), 2021)
This study examines the information content in political events in 2019, namely the appointment of the president and vice president and the announcement of the Kabinet Indonesia Maju. Market reaction is measured by abnormal returns, security return variability, and trading volume activity. The observation period in this study was five days before and after the event, with a sample of 20 companies affiliated with the winner of the election and 25 companies at the announcement of the Indonesian Maju Cabinet. The results of hypothesis testing indicate that there is a difference in the average abnormal return in the event of the appointment of the elected president and vice president, but there is no difference in security return variability and trading volume activity. Furthermore, hypothesis testing shows that there is a significant difference in average trading volume activity before and after the announcement of the Kabinet Indonesia Maju, but there is no difference in abnormal return and security return variability. Keywords: Market Efficiency; Event Studies; Abnormal Returns; Security Return Variability; Trading Volume Activity.